Architectural Historiography and Fourth Wave Feminism. Issue 1 (18th December 2020) - Lange, Torsten; Pérez-Moreno, Lucía C.
Abstract : Over the course of the last decade, women from all over the world and from different social and cultural backgrounds continued to strive for equal rights in the face of discrimination, sexism, and misogyny. Utilizing new tools and strategies for communication, this 'fourth wave' of feminist thinking and activism is characterized by its commitment to a 'diversity of purpose' that recognises intersectionality as a key issue of our time and questions established sex/gender systems and gender as a binary category. This Special Collection explores the impact of current feminist discourse on architectural historiography. It offers critical debate on the legacy of second and third wave feminism, and asks for the ongoing relevance of the concerns and methodologies. It also highlights the potential of new strategies for documenting and researching the work of women architects, investigating the possibilities of digital tools and networked knowledge. Moreover, the collection considers histories of feminist architectural writing in relation to non-canonical geographies and takes a broader view to include LGBTIQ+ perspectives on the built environment. It offers diverse explorations of these key issues and presents necessary reflections to widen feminist enquiries in architectural discourse.